Antiviral Treatment and One-Year Follow-Up of Chronic Hepatitis B Patients in Bandung: An Observational Study - Eka Surya Nugraha; Stefanie Hadi Supriami; Nur Atik; Nenny Agustanti; Yudi Wahyudi; Dolvy Girawan; M Begawan Bestari; Siti Aminah Abdurachman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Hepatitis B Virus (HBV) is a health problem that has chronically infected 257 million globally. Appropriate therapy is immensely needed to prevent disease progression to cirrhosis and hepatocellular carcinoma (HCC). Moreover, routine monitoring is required to assess the efficacy of the given treatment. This study aims to describe the treatment and its follow-up outcomes among chronic HBV patients after one year of therapy in Bandung.Method: This was a cross-sectional descriptive study with a data sampling method obtained from assessing the medical records of treated chronic HBV outpatients at the Gastrohepatoenterology Clinic of Hasan Sadikin Hospital Bandung from 2018 to 2020. Laboratory findings before and after one year of therapy were further assessed.Results: Out of 107 patients treated, the proportion of tenofovir was 72.90%, telbivudine 16.80%, lamivudine 8.40%, and interferon group 1.90%. There were 52.30% of patients who did follow-up visits after one year of therapy. The therapeutic outcome rate was evaluated among total patients with the criteria of decreasing AST (91.18%) and ALT levels (93.10%) levels, reduction of HBV-DNA values (100%), and HBeAg seroconversion (14.29%).Conclusion: The most given therapy among chronic HBV outpatients was tenofovir. The follow-up rate of patients after one year of treatment was 52.30%. Overall, antiviral therapies produced decreases in liver laboratory parameters, HBV-DNA, and HBeAg.